Zastosowanie automatycznej identyfikacji w logistyce: The use of automatic identification in logistics - Markiewicz, Tomasz (Management and Administration Journal, 2021)
Continuously developing economy entails a number of changes. More often people‟s work is enhanced or replaced by specialized equipment. This article describes the use of information systems in logistics. Methods such as barcode and RFID system were discussed.